(untitled) (In Factis Pax: Journal of Peace Education and Social Justice, 2022)
The decades of persistent and protracted conflict amid despair hopes become structural in nature. It permeates into the normal life-course of people making the common masses unaware of its destructive and long-run negative impacts. The survival becomes a priority and people tends to be insensitive towards innate feelings associated with the aesthetic sense. Once people are accustomed about the loss of aesthetic sense especially in the stark presence of aestheticism it proves its presence as a structural problem creeping into systems of various kinds. The current essay is a novel attempt to associate the loss of aesthetic sense to continuation of structural conflict. The study is based in the low-intensity conflict region of Jammu and Kashmir, India. The region presents a peculiar case of aesthetic environment called “heaven on earth” amid the infamous “most militarized zone in the world”, and reports some instances of people to support the conflict-aesthetic travesty.